Head Roll-Tilt Subjective Visual Vertical Test in the Diagnosis of Persistent Postural-Perceptual Dizziness. Issue 10 (December 2021) - Yagi, Chihiro; Morita, Yuka; Kitazawa, Meiko; Nonomura, Yoriko; Yamagishi, Tatsuya; Ohshima, Shinsuke; Izumi, Shuji; Takahashi, Kuniyuki; Wada, Yoshiro; Kitahara, Tadashi; Horii, Arata
Abstract : Objective: To examine the validity of head roll-tilt subjective visual vertical (HT-SVV) in diagnosing persistent postural-perceptual dizziness (PPPD). Study Design: Retrospective review. Setting: Tertiary referral center. Patients: Sixty-one patients with PPPD, 10 with unilateral vestibular hypofunction (UVH), and 11 with psychogenic dizziness (PD), showing chronic vestibular symptoms for >3 months. Interventions: Head-tilt perception gain (HTPG, i.e., mean perceptual gain [perceived/actual tilt angle]) during right or left head tilt of approximately 30° (HT-SVV) and conventional head-upright SVV (UP-SVV) were measured. Bithermal caloric testing, cervical and ocular vestibular-evoked myogenic potentials (cVEMP and oVEMP), and posturography were conducted. Main Outcome Measures: Multiple comparisons were performed for the HT-SVV and other vestibular tests among the disease groups. A receiver operating characteristic curve was created to predict PPPD using HTPG. Results: HTPG was significantly greater in the PPPD group than in the UVH and PD groups. There were no significant differences in UP-SVV, cVEMP, oVEMP, and posturography (foam ratio and Romberg ratio on foam) among the disease groups, while the UVH group had the highest canal paresis compared to the other two groups. The area under the curve of the receiver operating characteristic curve for predicting PPPD was 0.764, and the HTPG value of 1.202 had a specificity of 95.2% for diagnosing PPPD. Conclusions: While conventional vestibular tests including UP-SVV, VEMPs, and posturography did not show abnormalities in PPPD, high HTPG in the HT-SVV test, an excessive perception of head tilt, can be a specific marker for discriminating PPPD from other chronic vestibular diseases. Abstract : Supplemental Digital Content is available in the text